Changes in rainfall seasonality in the Western Cape, South Africa: an exploration of methods for determining the start and end of the rainfall season - Ivey, Peter (Department of Statistical Sciences, 2021)
The aim of this thesis is to detect and analyse changes in seasonality in rainfall for various groups of weather stations in the Western Cape area. Weather stations with similar seasonal patterns are firstly grouped together using certain clustering algorithms. The start and end of the rainfall season dates for the different groups of weather stations are estimated and then compared over time to determine whether there have been any changes. Once these start and end of season dates have been estimated, the length of the rainfall season is estimated and compared over time. Studies have been performed globally and over southern Africa attempting to analyse rainfall patterns and changes. However, rainfall is the most unstable climate variable in terms of time and space and thus, it is really difficult to predict (Yaman, 2018). Most studies have pointed toward an increase of extreme events on both sides of the scale i.e. more intense flooding and more severe drought being experienced. Some places are also starting to experience more rainfall than before whilst other places are starting to experience more drought. The impacts of these rainfall changes are already being experienced with many areas being forced to adapt to the new conditions. Many better decisions can be made with a better understanding of how rainfall seasons are changing. In the agricultural industry, better informed decisions about when the rainfall season is likely to start and end can result in more optimal yield from crops. Changes in rainfall can also affect the type of crops that should be planted. Farmers will also be able to better prepare for drought seasons if they are better informed as to when these drought periods will likely occur. In terms of disaster risk management, the more that is known about rainfall patterns, the better prepared regions can be for the inevitable increase in extreme events. Cities can put in better systems now in order to deal with potential future crises. Cape Town is an example of a city that could have possibly been better prepared for the current drought crisis if there was a better understanding of rainfall trends. Hopefully in the future, with more accurate information about rainfall, it can rather be an active process than a reactionary process to the current climate conditions.